2017
DOI: 10.1016/j.knee.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of motion at the bone–implant interface after total knee arthroplasty: The role of implant design and surgical fit

Abstract: In conclusion, long stemmed prostheses appeared less susceptible to surgical cut errors than short stemmed and stemless implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Prosthesis selection varies depending on the patient, the technique preferred by the surgeon and available prosthesis options. However, the general approach includes using long-stem prostheses in the knees with bone defects and constrained prostheses are used for the knees with ligament imbalance (18).Constrained prostheses were used in three of the patients. One of these patients was the patient who developed an infection after revision and had associated serious bone defect and the other two patients were the ones in whom multiple revisions were had to be performed for the diagnosis of persistent instability.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthesis selection varies depending on the patient, the technique preferred by the surgeon and available prosthesis options. However, the general approach includes using long-stem prostheses in the knees with bone defects and constrained prostheses are used for the knees with ligament imbalance (18).Constrained prostheses were used in three of the patients. One of these patients was the patient who developed an infection after revision and had associated serious bone defect and the other two patients were the ones in whom multiple revisions were had to be performed for the diagnosis of persistent instability.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that aseptic, osteolysis and infection are the most common causes of total knee arthroplasty (TKA) failure. The study examined the role of implant design features and stems in resisting loosening, and explored the sensitivity of the implants to a loose surgical instrument due to oscillation [5].…”
Section: Literature Review 21 Implantmentioning
confidence: 99%
“…As widely recognised, the fixation method (cemented or cementless) and implant configurations (stemmed or stemless) can have a major effect on the movement between bone and implant. Also, recent studies have shown that implant design features, such as the size and placement of the distal femoral pegs, the anteroposterior slope of the femoral component, and the angle of the implant, may have a substantial role in the long-term durability of prosthesis [5]. There are many different types of knee arthroplasty implants depending on the number of knee compartments to be replaced and the stability of the ligaments.…”
Section: Literature Review 21 Implantmentioning
confidence: 99%
“…This research led to the development of the porous implants. Furthermore, in [ 19 ], a computational model was developed that explored the implant design features that resisted loosening. The finite element analysis of the contact mechanics of the press-fit hip implants also showed that minimizing the micromotion, especially during the post-operative situation, should provide an adequate stability for the implant to promote the osseointegration [ 20 ].…”
Section: Introductionmentioning
confidence: 99%